A Review of Vessel Traffic Services Systems Operating in Poland in Terms of Their Compliance with International Legislation - Wojciech Durczak; Ludmiła Filina-Dawidowicz (Applied Sciences)
Vessel Traffic Services (VTS) systems are complex systems facilitating decision-making processes and integrating technical infrastructure, aiming to ensure the safety of ship traffic and marine environment protection in indicated water areas. Such services are offered in Poland in selected regions. These systems operate based on guidelines established by the International Maritime Organization (IMO) and European Parliament; therefore, they should be constantly developed and adjusted to current regulations. The aim of this article is to review and assess the adjustment of VTS systems operating in Poland to current selected regulations introduced by the IMO and European Parliament. A comparative analysis and evaluation of three VTS systems operated in Poland was carried out. In addition, the impact of VTS systems on the development of the trans-European transport network was examined. It was stated that the investigated VTS systems’ current adjustment to analyzed regulations is different depending on the systems’ configuration and possessed infrastructure, parameters of fairways, traffic regulations and other criteria. Based on the achieved research results, recommendations to improve the VTS systems in Poland were proposed. The research outcomes may be interesting for the managers of maritime administrations, ports’ authorities, and other decision-makers responsible for safe navigation and traffic management.